The effect of organizational communication, transformational leadership and organizational learning to OSH performance A Case Study in PT WASKITA KARYA - Kholil, Kholil; K, Amri (Archives of Business Research, 2022)
Cases of work accidents are still happening today, including the construction service company. It indicates that the safety performance of construction service companies is not optimal, so it is important and needs to be investigated, especially safety culture, organizational communication, learning organization, and transformational leadership. Hence, this study explores the role of organizational communication in mediating the influence of transformational leadership and learning organization on safety culture and safety performance. The study used a quantitative approach through a survey with a questionnaire instrument designed on a Likert scale. The participant is 218 workers of PT. Waskita Karya (Persero) Tbk. Data analysis using structural equation modeling. The results showed that transformational leadership, learning organization, and safety culture had a positive and significant direct effect on work safety performance and safety culture, in addition the result also confirm that the key success factor for safety performance is organizational communication. Based on these findings, practically it is recommended that organizational communication among the workforce needs to be improved continuously to make a greater contribution to safety culture and performance.